Investigation of internal dynamics of soliton with the help of traveling wave soliton solution of Hamilton amplitude equation - Yokus, Asif; Isah, Muhammad Abubakar (Springer, 2022)
The phi(6)-model expansion technique is used in this work to obtain dark, bright, periodic, singular, dark-bright, combined singular soliton and rational solutions to the Hamiltonian amplitude equation. This equation is used to analyze the stability of the exact solutions as well as to determine modulated wave train instabilities. The obtained results are mostly applicable in the study of nonlinear waves in plasma in the setting of a non-magnetized fluid-type plasma, the dispersion of the Langmuir (electrostatic) wave when it generates some low-frequency acoustic waves, such as the ion-acoustic wave, and other fields. The behavior of the traveling wave is analyzed using the frequency values, which is one of the internal dynamics of the dark soliton. This discussion is supported by graphs and the effects on wave behavior of different densities are simulated.
Keywords: phi(6)-model expansion method; Hamilton amplitude equation; Traveling wave solution; Wave frequency; Internal dynamics of soliton